Comparative Study of Diode Laser Versus Intense Pulsed Light (IPL) for the management of Hirsutism in Sulaimani Government - Tahir Saeed, Burhan (Kurdistan Journal of Applied Research, 2020)
Hirsutism defined as excessive hairiness, hirsutism can negatively affect individuals, particularly females. Hirsutism has been attributed to the presence of high levels of androgen. There are different procedures to treat hirsutism; however, diode laser and intense pulsed light (IPL) are the most common methods. The present study was carried out in order to compare diode laser and IPL procedures regarding their effectiveness in decreasing hirsutism, patient satisfaction, and pain level. The present cross-sectional prospective study was carried out on 66 patients with hirsutism who regularly visited a dermatology clinic in Sulaimani, Kurdistan Region-Iraq over a period of 8 months from February to October 2020. They were assigned into a diode laser group (n=35) and an IPL group (n=31). Each patient had 8 laser sessions, once every month. Required data were collected through photos taken in every session. The collected data were analyzed through Statistical Package for the Social Sciences (version 22.0). The patients’ mean age was 33.12 years. Over 53% and 35% of them had a family history of first- and second- degree hirsutisms, respectively. Both procedures led to good and very good primary outcomes in 43.9% and 36.4% of the patients, respectively. Patient satisfaction was high in 42.4% of them. Our research has showed that IPL has fewer side effects (p-value<0.001), better primary outcome (p-value<0.001), and better patient’s mood (p-value<0.002). The two procedures led to similar level of patient satisfaction, and they were not significantly different in this regard (p-value=0.3). In terms of hair types, the two procedures were significantly different (p-value<0.001), such that IPL was better for thin hair, while diode laser for thick hair. Both diode laser and IPL procedures were found to be efficient in terms of primary outcome, patient satisfaction, and patient’s mood. However, diode laser is proper for dark-skinned patients with thick hair and IPL for thin hair. Diode laser was found to be better choice for our patients because most clients in the region are dark-skinned with thick hair.